The Implications of Consumer Protection Legislation for Hotels and Guests in South Africa - Mohamed, Raeesah; Reddy, Karunanidhi; Naidoo, P. M. (Journal of Economics and Behavioral Studies, 2017)
During the apartheid era, consumers in South Africa, based on their race and ethnicity, were restricted when concluding contracts, as there was no open market trade. As consumers, hotel guests could also be victims of unfair business practices. Hotels use standard form contracts that may include unfair terms that favour the business and which are over-protective of business interests. A significant percentage of the population have low literacy levels, which severely disadvantage them when it comes to understanding the content and consequence of contracts. The Consumer Protection Act (CPA) introduces wide-ranging legal measures to protect consumers, including hotel guests, from exploitation and abuse in the marketplace and sets out comprehensive obligations for hotels. This article provides a descriptive critique based on literature and describes the challenges faced by hotel guests and discusses the implications of the Act for hotels and guests. It concludes that not only does the CPA advocate ethical business practices that are mandatory for hotels, but it also introduces a range of rights and protection for guests as consumers. The CPA has introduced a shift in contract law from a standpoint which allowed the parties the freedom to choose the content of the contract to one where fairness and transparency is imperative, as protection in terms of legislation compensates for the weaker bargaining position of the consumer.